2003
DOI: 10.1097/01.wcb.0000093324.07718.d4
|View full text |Cite
|
Sign up to set email alerts
|

Translational Paradigms in Cerebrovascular Gene Transfer

Abstract: Summary:Gene transfer involves the use of an engineered biologic vehicle known as a vector to introduce a gene encoding a protein of interest into a particular tissue. In diseases with known defects at a genetic level, gene transfer offers a potential means of restoring a normal molecular environment via vectormediated entry (transduction) and expression of genes encoding potentially therapeutic proteins selectively in diseased tissues. The technology of gene transfer therefore underlies the concept of gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 80 publications
(204 reference statements)
0
2
0
1
Order By: Relevance
“…8,12 Caspase-3 activity was measured as described previously. 13 Measurements of Nitrate/Nitrite Levels and Nicotinamide-Adenine Dinucleotide Phosphate Oxidase Activity NO levels (in the form of nitrate/nitrite) in brain extracts were measured at day 3 after MCAO as described previously. 14 Reduced nicotinamideadenine dinucleotide phosphate (NADH) oxidase activity was measured by lucigenin-enhanced chemiluminescent detection of superoxide in a luminometer (TD-20/20, Turner Designs Inc).…”
Section: Western Blot Analyses Of Akt and Glycogen Synthetase Kinase-mentioning
confidence: 99%
“…8,12 Caspase-3 activity was measured as described previously. 13 Measurements of Nitrate/Nitrite Levels and Nicotinamide-Adenine Dinucleotide Phosphate Oxidase Activity NO levels (in the form of nitrate/nitrite) in brain extracts were measured at day 3 after MCAO as described previously. 14 Reduced nicotinamideadenine dinucleotide phosphate (NADH) oxidase activity was measured by lucigenin-enhanced chemiluminescent detection of superoxide in a luminometer (TD-20/20, Turner Designs Inc).…”
Section: Western Blot Analyses Of Akt and Glycogen Synthetase Kinase-mentioning
confidence: 99%
“…7,34,35 In the present study, we found that intracisternal protein transduction using an 11R-fusion protein selectively delivered this protein into cerebral vessels, and the delivered protein was especially transduced into the tunica media (smooth muscle layer) of the BA (Figure 3), even when it had been exposed to SAH (Figures 4, 5). This finding suggests that this protein transduction method may be a more effective therapeutic The high expression of 11R-EGFP was maintained when the BAs were kept on incubating with 11R-EGFP for 12 hours ex vivo (Figure 1).…”
Section: Discussionmentioning
confidence: 85%
“…A literatura enfatiza que a patogênese do vasoespasmo cerebral tardio está relacionada com vários processos patológicos que incluem a destruição endotelial e A exposição da hemoglobina nas cisternas acaba sendo a mesma ligada hepaticamente e produzindo a haptoglobina (HP) que possui duas isoformas e está relativamente ligada ao processo da inflamação 186 .…”
Section: E2 Fisiopatologia Do Vasoespasmo Encefálicounclassified